The 13th warrior [videorecording (DVD)] - Goldsmith, Jerry (Touchstone Home Video, 1999)
After being warned by a fortune-teller that their fight against legendary creatures is doomed to failure unless they have a 13th warrior, a travelling ambassador (Banderas) is given no choice but to join a group of fierce fighters.